Final results of the HEALING IIB trial to evaluate a bio-engineered CD34 antibody coated stent (Genous™Stent) designed to promote vascular healing by capture of circulating endothelial progenitor cells in CAD patients - den Dekker, W; Houtgraaf, J; Onuma, Y; Benit, E; de Winter, R; Wijns, W; Grisold, M; Verheye, S; Silber, S; Teiger, E; Rowland, S; Ligtenberg, E; et al. (2011)
Objective: To assess the safety and efficacy of the Genous™ endothelial progenitor cell (EPC) capturing stent in conjunction with HmG-CoA-reductase inhibitors (statins) to stimulate EPC recruitment, in the treatment of patients with de novo coronary artery lesions. Methods and results: The HEALING IIB study was a multi-center, prospective trial, including 100 patients. The primary efficacy endpoint was late luminal loss by QCA at 6-month follow-up (FU). Although statin therapy increased relative EPC levels by 5.6-fold, the angiographic outcome at 6 month FU was not improved in patients with an overall in-stent late luminal loss of 0.76 ± 0.50 mm. The composite major adverse cardiac events (MACE) rate was 9.4%, whereas 6.3% clinically justified target lesion revascularizations (TLRs) were observed. 2 Patients died within the first 30 days after stent implantation due to angiographically verified in-stent thrombosis. At 12 month FU, MACE and TLR increased to 15.6% and 11.5% respectively and stabilized until 24 month FU. 18 Month angiographic FU showed a significant decrease in late luminal loss (0.67 ± 0.54, 11.8% reduction or 10% by matched serial analysis, P= 0.001). Conclusion: The HEALING IIB study suggests that statin therapy in combination with the EPC capture stent does not contribute to a reduction of in-stent restenosis formation for the treatment of de novo coronary artery disease. Although concomitant statin therapy was able to stimulate EPC recruitment, it did not improve the angiographic outcome of the bio-engineered EPC capture stent. Remarkably, angiographic late loss was significantly reduced between 6 and 18 months. © 2011 Elsevier Ireland Ltd.